(3+2a)(2a-3)=

Simple and best practice solution for (3+2a)(2a-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+2a)(2a-3)= equation:


Simplifying
(3 + 2a)(2a + -3) = 0

Reorder the terms:
(3 + 2a)(-3 + 2a) = 0

Multiply (3 + 2a) * (-3 + 2a)
(3(-3 + 2a) + 2a * (-3 + 2a)) = 0
((-3 * 3 + 2a * 3) + 2a * (-3 + 2a)) = 0
((-9 + 6a) + 2a * (-3 + 2a)) = 0
(-9 + 6a + (-3 * 2a + 2a * 2a)) = 0
(-9 + 6a + (-6a + 4a2)) = 0

Combine like terms: 6a + -6a = 0
(-9 + 0 + 4a2) = 0
(-9 + 4a2) = 0

Solving
-9 + 4a2 = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 4a2 = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 4a2 = 0 + 9
4a2 = 0 + 9

Combine like terms: 0 + 9 = 9
4a2 = 9

Divide each side by '4'.
a2 = 2.25

Simplifying
a2 = 2.25

Take the square root of each side:
a = {-1.5, 1.5}

See similar equations:

| -12-3n=6(12n-2) | | 17+11v=8+4(-7+12v) | | -3+4r=-23-r | | 0=16t-t^2+40 | | 3x-12x=10-4x | | 4=100y^2 | | -3(1+n)+7n=5(2+n) | | 12+7-6x-7=4-7x | | 0=16-t^2+40 | | 5x-5x-1=2x+5 | | 33-3a=6(a-5) | | 8(7r-1)=-8+2r | | 8(-8+4x)=-36+4x | | 8(-8+4x)=36+4x | | 2(4-4n)=-6+6n | | 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m | | r^3+3r-10=0 | | 6x^2+3x-c=0 | | lg*(x-2)+lg*(x+3)=lg*14 | | (x+3i)(y-2i)=18+6i | | 11r+1=5r+19 | | 6m-12=2m+8 | | 5y-27=3y-5 | | x^2+(k-2)x+(k+3)=0 | | (7+w)(5w-2)=0 |

Equations solver categories